Production of boiler and furnace fuels from domestic wastes (polyethylene items) - Grigorov, Andrey; Mardupenko, Aleksey; Sinkevich, Irina; Tulskaya, Alena; Zelenskyi, Oleg (My University, 2018)
The results of the thermal destruction of solid domestic waste (which are polyethylene items) were presented for batch-type laboratory equipment. According to the modern requirements of EU for the amount of sulphur in fuel and boiler fuels, polyethylene items are a valuable source for pro-duction of these fuels. During atmospheric heating of the raw material in reactor the intensive destruction of polyethylene can be observed in the range of temperature 560–580 K. It has been defined the composition of products of polyethylene thermal destruction: 95 % (mass.) of liquid hydrocarbons, 4,5 % (mass.) of light hydrocarbon gases and 0,5 % (mass.) of coke. Fractionation of liquid hydrocarbons allows to separate 15 % (mass) of fraction 340-488 K, 14 % of fraction 406-518 K, 43 % of fraction 438-546 K and 27 % of residue (>623ºС fractions). Liquid products can be applied for production of boiler and furnace fuels independently and in a mixture with the petroleum processing products in different ratio.
Keywords: polyethylene items; thermal destruction; reactor; boiler fuel; fractionation; residue; aromatic hydrocarbons